Pandemics and aggregate demand: A framework for policy analysis - Peter Flaschel; Giorgos Galanis; Daniele Tavani; Roberto Veneziani (Hans-Böckler-Stiftung, Macroeconomic Policy Institute (IMK), Forum for Macroeconomics and Macroeconomic Policies (FMM), 2021)
This paper studies the interaction between epidemiological dynamics and the dynamics of economic activity in a demand-driven model in the structuralist/post-Keynesian tradition. On the one hand, rising aggregate demand increases the contact rate and therefore the probability of exposure to a virus. On the other hand, rising infection lowers aggregate demand because of reduced household spending. The resulting framework is well-suited for policy analysis through numerical exercises. We show that, first, laissez-faire gives rise to sharp fluctuations in demand and infections before herd immunity is achieved. Second, absent any restrictions on economic activity, physical distancing measures have rather limited mitigating effects. Third, lockdowns are effective, especially at reducing death rates while buying time before a vaccine is available, at the cost of a slightly more pronounced downturn in economic activity compared with alternative policies. This casts some doubt on the so-called "lives versus livelihood" policy trade-off. However, we also highlight the importance of policies aimed at mitigating the effects of the epidemic on workers' income.
Keywords: I1; E6; E25; E12; H0; 330; pandemic; aggregate demand; distribution; public policy